2011
DOI: 10.1111/j.1365-2214.2011.01334.x
|View full text |Cite
|
Sign up to set email alerts
|

Beyond behavioural observations: a deeper view through the sensory reactions of children with profound intellectual and multiple disabilities

Abstract: Data here presented may have implications for the development and the emotional well-being of individuals with profound intellectual and multiple disabilities in that it suggests that reactions to, and potential appraisals of, sensory stimuli may occur despite the lack of consistent observable behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 41 publications
1
12
0
1
Order By: Relevance
“…In general, the psychophysiological results supported these behavioural findings. However, there were some (slightly) different or contradicting findings in comparison with the behavioural observations (this lack of consistency is also described in previous research; Koolhaas et al, 2011;Lima et al, 2011;Parihar, Hattiangady, Kuruba, Shuai, & Shetty, 2011). A first difference between behaviour and physiology to be noted is situated in the arousal during comfort.…”
Section: Discussionsupporting
confidence: 57%
“…In general, the psychophysiological results supported these behavioural findings. However, there were some (slightly) different or contradicting findings in comparison with the behavioural observations (this lack of consistency is also described in previous research; Koolhaas et al, 2011;Lima et al, 2011;Parihar, Hattiangady, Kuruba, Shuai, & Shetty, 2011). A first difference between behaviour and physiology to be noted is situated in the arousal during comfort.…”
Section: Discussionsupporting
confidence: 57%
“…; Lima et al . ). Further research should combine these physiological and behavioural measures to further investigate the relationship between the valence of emotion and attention.…”
Section: Resultsmentioning
confidence: 97%
“…The role of attention in the emotions of people with severe or profound ID should however be investigated in more detail using a direct measure of attention. There have been two studies that have shown that both behavioural observations and physiology can give information about the attention of people with severe or profound ID Lima et al 2013). Further research should combine these physiological and behavioural measures to further investigate the relationship between the valence of emotion and attention.…”
Section: Resultsmentioning
confidence: 99%
“…Heart rate, in turn, was continuously recorded throughout all experimental sessions, with the noninvasive ambulatory Biopac MP100 Data Acquisition System (Biopac Systems, Santa Barbara, CA, USA) (following Lima and colleagues [9]). As for behavioral data, consistent heart rate responses were considered as numerical changes from baseline occurring in all experimental sessions.…”
Section: Can You Help When It Hurts? Dogs As Potential Pain Relief Stmentioning
confidence: 99%